PERANAN PENDIDIKAN AGAMA ISLAM DALAM MEMPERBAIKI MORAL PESERTA DIDIK DI SEKOLAH - Ahmad Miswar Nasution (Jurnal Ilmu Tarbiyah Dan Keguruan (JITK), 2023)
This research aims to find out how important religious education is in integrating values ​​in all educational activities. The values ​​contained in Pancasila as the basis of education do not conflict with Islamic values ​​(tauhid). Viewing humans as physical and spiritual creatures who have the potential to become dignified human beings, education aims to develop potential, to become human beings who have faith and devotion to God Almighty, are virtuous, have noble character and are responsible for themselves as well as for society. Religious Education Islam is an effort to obey Allah's provisions so that students can understand Islamic sciences in implementing Allah's provisions in their entirety. This provision is to understand its laws which are called Khauliyyah verses. The meaning of the Khauliyyah verses themselves is Sunnatullah/laws. God's law.